1969
DOI: 10.1038/2241299a0
|View full text |Cite
|
Sign up to set email alerts
|

Water-induced Weakening of Hornblende and Amphibolite

Abstract: FUEL cells with acid electrolyte, such as dilute sulphurin acid, have the advantage over those with alkaline electrolyte that carbon dioxide is not absorbed by the electrolyte. In principle it is therefore possible to use organic fuels,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The differential stress of deformed amphibolite under wet conditions was only ∼30 to 50% of that under dry conditions at the same temperature and strain rate ( Table 1 ). This water-induced weakening of amphibolite coincides with the results of earlier experimental studies 21 25 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The differential stress of deformed amphibolite under wet conditions was only ∼30 to 50% of that under dry conditions at the same temperature and strain rate ( Table 1 ). This water-induced weakening of amphibolite coincides with the results of earlier experimental studies 21 25 .…”
Section: Resultssupporting
confidence: 90%
“…Previous experimental studies of amphibolite primarily focused on the mechanical behaviour of amphibole under uniaxial compression. Water weakening of amphibolite was observed at a temperature of 800 °C and confining pressures of 0.5–2 GPa due to the dehydration reaction of hornblende 21 22 23 . The experimentally deformed amphibole in earlier studies showed a crystal plasticity at pressures of 0.5–2 GPa and temperatures of 600–800 °C (refs 23 , 24 ), with a slip system of (100)[001] and ( 1 01) twinning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Summers and Byerlee, 1977). Riecker and Rooney (1969) and Murrell and Ismail (1976) found similar effects in the experimental deformation and dehydration of amphibole and chlorite, respectively. All of these examples illustrate interrelationships of type (a) above.…”
Section: Examples Of Experimental Studiesmentioning
confidence: 65%
“…However, xenolith studies suggest that the added volatiles are usually taken up in amphibole overgrowths on clinopyroxene, rather than being incorporated into olivine, and, thus, will lower the solidus of the peridotite by several hundred degrees Celsius relative to that of anhydrous peridotite (Olafsson & Eggler 1983). Although appropriate experimental data are limited, it seems likely that amphibole (Riecker & Rooney 1969) will be just as strong as clinopyroxene (Kirby & Kronenberg 1984), and so there is as yet little reason to think that volatile-enriched major-element-depleted peridotite should be any weaker than normal anhydrous fertile peridotite (Turner & Hawkesworth 1995). On the contrary, the increased thickness and resultingly cooler geotherm, and the opx-rich mineralogy, combine to make Archaean lithosphere significantly stronger than Proterozoic and younger lithosphere; a feature presumably linked to its longer survival.…”
Section: (E) Volatilesmentioning
confidence: 99%